Volume 9: Ocean Renewable Energy 2015
DOI: 10.1115/omae2015-41388
|View full text |Cite
|
Sign up to set email alerts
|

Control of an Open-Loop Hydraulic Offshore Wind Turbine Using a Variable-Area Orifice

Abstract: The viability of offshore wind turbines is presently affected by a number of technical issues pertaining to the gearbox and power electronic components. Current work is considering the possibility of replacing the generator, gearbox and electrical transmission with a hydraulic system. Efficiency of the hydraulic transmission is around 90% for the selected geometries, which is comparable to the 94% expected for conventional wind turbines. A rotor-driven pump pressurises seawater that is transmitted across a lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Equations ( 6)-( 9) in Section 2.2 are used in both the Alpha and Beta models. The Beta model introduces a nested PID control loop, based on previous work by Buhagiar et al [39], to regulate power requirements and maintain optimal speed based on the bucket-to-speed ratio previously mentioned in Section 2.2 [27]. Moreover, the Pelton turbine's inertia and damping are also considered to calculate the bucket torque to be matched to the generator's torque for power generation, a step which is omitted in the Alpha model.…”
Section: The Discharging Modelmentioning
confidence: 99%
“…Equations ( 6)-( 9) in Section 2.2 are used in both the Alpha and Beta models. The Beta model introduces a nested PID control loop, based on previous work by Buhagiar et al [39], to regulate power requirements and maintain optimal speed based on the bucket-to-speed ratio previously mentioned in Section 2.2 [27]. Moreover, the Pelton turbine's inertia and damping are also considered to calculate the bucket torque to be matched to the generator's torque for power generation, a step which is omitted in the Alpha model.…”
Section: The Discharging Modelmentioning
confidence: 99%
“…On the basis of the Delft Offshore Turbine concept, Daniel Buhagiar et al studied the variable water pump‐valve open‐loop system and proposed the feed‐forward control (FFC) to maintain the pipeline pressure in Buhagiar et al 111 Comparing the FFC strategy and the method that is referred to as feedback with feed‐forward compensation (FB‐FFC) in Buhagiar et al, 112 the simulation results indicate that the latter control strategy is better. And Laguna et al simulate the transmission structure in a wind farm, and results indicate that the individual wind turbines are able to operate within operational limits 113…”
Section: The Hydraulic Technology Applications In Wind Turbinementioning
confidence: 99%
“…A variable area nozzle is included at the end of thepipeline. A control scheme [7] isimplemented to adjust the cross‐sectional area of the nozzle continuously withwind speed to maintain a constant pressure drop across the nozzle. In this way,a constant DSW jet velocity is maintained, enabling the fixed‐speed Pelton wheelto be connected to a synchronous electrical generator and operated at constantspeed without the need for an electronic inverter.…”
Section: System Descriptionmentioning
confidence: 99%
“…A number of offshore turbines can be interconnected to a centralised hydroelectric power plant using a hydraulic pipeline network. Numerical studies have demonstrated the technical feasibility of the latter approach through the integration of novel control schemes [6, 7]. However, the transmission efficiency of fluid power through hydraulic pipelines is significantly lower than that encountered in electrical power transmission.…”
Section: Introductionmentioning
confidence: 99%